ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERALIHAN FUNGSI LAHAN KELAPA SAWIT KE LAHAN PADI SAWAH DI DESA BARU PASAR VIII, KABUPATEN LANGKAT - Irama, Hera; Sintong, Mahara (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
This study aims to analyze the factors influencing the conversion of oil palm land to paddy fields in Baru Pasar VIII Village, Hinai District, Langkat Regency. The population in this study were all farmers in Baru Pasar VIII Village who had converted their land from oil palm to paddy fields in the last 5 years, totaling 40 farmers. The sample in this study was 20 farmers who had converted their land in the last 5 years. Data collection techniques in this study were carried out through observation, interviews, and documentation. The results of this study indicate that low income from oil palm encourages farmers to switch to paddy fields, thus increasing their income. This transition is supported by other factors such as capital, selling prices, land conditions, seeds, and fertilizers. The land conversion process also ran smoothly without any significant obstacles. This study recommends that farmers first consider the supporting and inhibiting factors of a particular agricultural commodity to be used so that land management can be carried out more effectively.